Design Of Split AC Modification Become Air Conditioning Of Geothermal Open System - Widiyatmoko,Fuad Zainuri,Adi Suryadi,Imam Wahyudi ,Abdul Azis Abdillah ,Hendradinata (International Conference on Industrial Revolution for Polytechnic Education, 2019)
Air conditioning system is a system used to condition the air in accordance with the desired design. The use of air conditioning tools such as buildings and residential. The type of air conditioner commonly used at home and office is a type of split air conditioner. AC geothermal system is an air conditioning technology that utilizes the temperature of the earth. There are 2 types of geothermal system conditioning. That is an open system and a closed system. Research has been carried out on modifying split air conditioners into geothermal AC system, using a closed system. The problem that arises is what if there is a location that can facilitate the use of an open geothermal system. Of course this will be easier and cheaper to implement than a closed system, with supporting records of open system available free of charge. This design is carried out to provide an alternative geothermal air conditioning system. Based on the discussion, it can be concluded that air conditioning with modified AC split into an open geothermal system can be carried out if there are ponds / rivers / lakes near buildings that use split air conditioners, and the implementation of split AC modifications allows increased efficiency of energy use in the building / house